(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Gem therapy is old. It is referenced in Unani framework and point by point information and most extreme practice is required. The gem therapy takes a shot at the idea of hues vitality can be called as shading therapy. The cutting edge science has watched the huge impact of hues on the human body. This therapy is innocuous with no reaction, and may resolve numerous prospective issues for the control of issues excited. The center quality of Gemstones lies in the hues they transmit. Sun beams going through a gemstone cause it to emanate a vast shading that is consumed by the body chakras. They are broadly used to recuperate physical and enthusiastic sufferings. What makes a gemstone particular, entrancing, and extraordinary are its shading, cut, straightforwardness and energy. This survey incorporates all subtleties of recuperating forces of Gem therapy. In short we can portray Psycho-neurobics as-’Technique of taking galactic essentialness present known to mankind by the force of cerebrum (the source is GOD) and after that trading it to mind and neurosystem’ We can retouch any kind of disease by psycho-neurobics and activate our seven imperativeness centers present in the body. The word psycho stays for ’mind’ as we take the huge imperativeness through the force of cerebrum. There are three sorts of neurobics Light neurobics, sound neurobics and easy neurobics in Psycho-neurobics we fuse all the three neurobics.